Pengembangan Nilai Toleransi Melalui Mata Pelajaran Pendidikan Kewarganegaraan di Pondok Pasantren Wustha Shuffah Hizbullah - Nendy Hamzah Laku; Fricean Tutuarima; Fatimah Sialana (Cetta: Jurnal Ilmu Pendidikan, 2022)
Tolerance really needs to be applied in every human being. Tolerance teaches humans to be able to coexist with others in growing awareness of the beauty of togetherness in a pluralistic society. The most appropriate effort to instill the value of tolerance is through general education in schools, especially through civic education. seen in the classroom learning process, subject teachers only focus on increasing knowledge, teachers also apply learning with group discussions and some are not in groups such as giving individual assignments to problems or conditions that occur in schools. in learning and how teachers involve students in the diversity that occurs in schools. The purpose of this study was to determine the development of tolerance values ​​through the implementation of civic education learning. The method used is descriptive qualitative research method. The results and conclusions in this study are the lack of knowledge of the value of tolerance in each subject makes some students not quite understand the essence of tolerance even though the value of tolerance is a value that reflects the character of the Indonesian nation. However, in fostering an attitude of tolerance for students in the Wustha Shuffah Hizbullah Islamic boarding school, all teachers must work together and set an example of mutual respect in front of students so that students can imitate them before students do so, the teacher first sets an example because the teacher is a guide for students in determining attitudes.